2017
DOI: 10.1016/j.geoderma.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Can Fe isotope fractionations trace the pedogenetic mechanisms involved in podzolization?

Abstract: a b s t r a c t a r t i c l e i n f oStable Fe isotopes have shown the potential for tracing pedogenetic processes. Large isotopic fractionations were especially observed in Podzols. Nevertheless, a clear link between isotopic fractionation and elementary processes still needs to be established. To spatially distinguish the mechanisms successively involved in pedogenesis, we studied a podzolic chronosequence from Vancouver Island (British Columbia, Canada). We analyzed depth variations in soil properties (pH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…The processes of mineral weathering, Al/Fe complexation and mobilization as well as leaching of alkaline and alkaline-earth cations rapidly TABLE 2 | C fractions: total (C T ), Stable (C S ), recalcitrant (C R ), mineral-protected (C MP ), oxidizable (C O ), bulk soil SOM C T /N T ratio (values are given ± one standard deviation); soil respiration rates (slope of the cumulative CO 2 emission with time, calculated by linear regression, and associated R²-values), and soil respiration rates normalized by the total SOC content (=SOM biodegradability). occur, in less than 60 years, i.e., between P3-270 years and P4-330 years (Vermeire et al, 2016;Fekiacova et al, 2017). Such a timing for incipient podzolization is in agreement with several studies reviewed in Sauer et al (2008), revealing the formation of a bleached E horizon after about 200-500 years.…”
Section: Acidification and Accumulation Of Secondary Mineral Phasessupporting
confidence: 91%
“…The processes of mineral weathering, Al/Fe complexation and mobilization as well as leaching of alkaline and alkaline-earth cations rapidly TABLE 2 | C fractions: total (C T ), Stable (C S ), recalcitrant (C R ), mineral-protected (C MP ), oxidizable (C O ), bulk soil SOM C T /N T ratio (values are given ± one standard deviation); soil respiration rates (slope of the cumulative CO 2 emission with time, calculated by linear regression, and associated R²-values), and soil respiration rates normalized by the total SOC content (=SOM biodegradability). occur, in less than 60 years, i.e., between P3-270 years and P4-330 years (Vermeire et al, 2016;Fekiacova et al, 2017). Such a timing for incipient podzolization is in agreement with several studies reviewed in Sauer et al (2008), revealing the formation of a bleached E horizon after about 200-500 years.…”
Section: Acidification and Accumulation Of Secondary Mineral Phasessupporting
confidence: 91%
“…More precisely, Fe isotopes in soils are sensitive to redox processes, to weathering processes and the formation of Fe-oxides, and to the formation of Fe-organic complexes. Light Fe isotopes are often enriched in soils containing secondary Fe phases (e.g., Wiederhold et al, 2007b;Poitrasson et al, 2008;Guelke et al, 2010;Kiczka et al, 2011;Yesavage et al, 2012;Liu et al, 2014;Fekiacova et al, 2017). This enrichment can be explained by the quantitative precipitation of light Fe-oxyhydroxides from light Fe isotopes preferentially released by proton-promoted mineral weathering (Chapman et al, 2009;Kiczka et al, 2010a), reductive mineral dissolution (e.g., Wiederhold et al, 2006Wiederhold et al, , 2007aWiederhold et al, , 2007b, and ligand-controlled mineral dissolution (Brantley et al, 2001(Brantley et al, , 2004Wiederhold et al, 2006Wiederhold et al, , 2007bBuss et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The differences between summer and late autumn are driven by regional changes of the groundwater table, while data from spring show a wide range of Fe isotope values, which might be ascribed to more local differences. For the formation of a distinctly negative Fe isotope ratio, soil formation processes are necessary. ,, Excluding the organic top layer, the upper soil horizons are dominated by mineral dissolution by organic acids and light Fe­(II) aq is released to the solution, , leaving the soil enriched in heavy Fe isotopes . Vertical percolation to underlying horizons results in a light Fe isotope ratio in soil solution and groundwater. , On the other hand, the Fe isotope ratio of the solid phase is more positive. , An in situ field experiment showed abiotic fractionation of Fe isotopes due to adsorption of Fe­(II) aq onto newly formed Fe­(III)­(oxy)­hydroxides .…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen-rich water was injected into reduced Fe­(II) aq -rich groundwater and resulted in a very light groundwater component (down to −2.60‰). Several studies have shown that dissolved Fe­(II) aq is partly oxidized and precipitates during transport through the unsaturated zone of soils, causing migrating soil water Fe to be enriched in the light Fe isotope. ,,,,,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation